Dampak White Collar Crime Bagi Pemerintah Dan Masyarakat - Azi Shohi Sitorus; Nabilla Rahmadani; Sahlan Sahlan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
White collar crime is differentiated from blue collar crime. If the term white collar crime is intended for officials and high-ranking state officials, blue collar crime is used to refer to all scandalous crimes that occur at lower levels with low quality and quantity. However, we must also know that crime at the lower level is also a trickle down effect. So, if we want to participate in various crimes that occur in government agencies, we have to start from white collar crime, not from blue collar crime.